1999
DOI: 10.1046/j.1365-2559.1999.00791.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MUC1 and MUC2 mucin gene products in Barrett's metaplasia, dysplasia and adenocarcinoma: an immunopathological study with clinical correlation

Abstract: Despite the large number of patients with Barrett's metaplasia and carcinoma, very few patients presented with dysplasia, implying that Barrett's oesophagus is a silent disease in the community presenting late as carcinoma. The study has demonstrated aberrant expression of MUC2 (an intestinal mucin) in Barrett's metaplasia and this expression is lost when the cells become dysplastic. The lack of MUC1 in dysplastic epithelium and its expression in carcinoma could be utilized as a marker which could differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
2
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 22 publications
6
53
2
4
Order By: Relevance
“…HOXB5, HOXB6, and HOXB7 can activate some, but not all the intestinal makers commonly expressed in BE (36)(37)(38). Although this finding could depend on the transient nature of the transfection, it indicates that in the cell line model tested these genes do not induce a full intestinal phenotype and that other transcriptional factors may be required.…”
Section: Discussionmentioning
confidence: 92%
“…HOXB5, HOXB6, and HOXB7 can activate some, but not all the intestinal makers commonly expressed in BE (36)(37)(38). Although this finding could depend on the transient nature of the transfection, it indicates that in the cell line model tested these genes do not induce a full intestinal phenotype and that other transcriptional factors may be required.…”
Section: Discussionmentioning
confidence: 92%
“…The differential diagnosis of melanocytic tumors is based on the expression of several proteins, such as S-100B [3, 4, 5]. HMB-45 or the recently introduced MART-1/Melan-A [4, 19]. S-100B is a useful marker since its expression is independent of the melanization [20], in contrast to other markers.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10] It is well known that Barrett's oesophagus consists of two secreted mucin phenotypes, namely gastricand intestinal-predominant mucin phenotypes, and that the latter phenotype has a more malignant potential. [11][12][13] A number of investigators have reported that…”
Section: Introductionmentioning
confidence: 99%